Deadbeat predictive current control of permanent magnet synchronous motor based on variable step-size adaline neural network parameter identification - Wang, Zhiqiang; Yang, Mingbo; Gao, Le; Wang, Zhixin; Zhang, Guozheng; Wang, Huimin; Gu, Xin (IET electric power applications, 2020)
The fast and stable inner current loop in the permanent magnet synchronous motor control system is the key factor that ensures the torque control performance of the motor. The deadbeat predictive current control has good dynamic response performance, but it depends heavily on the precise mathematical model of the controlled object. The parameter mismatch will degrade the control performance. A deadbeat predictive current control method based on online parameter identification is proposed in this study. This method does not need to inject additional d-axis current to identify the parameters during the operation of the motor; it only needs to make full use of the inherent phenomenon that the q-axis current changes when the load of the motor changes during operation, and perform parameter identification. Aiming at the problem that the effect of parameter identification is easily affected by motor speed, a new variable step-size neural network algorithm is designed in this study. The speed factor is introduced into step function to ensure the performance of the identification algorithm at a different speed. Finally, based on the new online parameter identification algorithm, the deadbeat predictive current control method is used to verify the experiment.